Diterpenoids from Blumea balsamifera and Their Anti-Inflammatory Activities - Xiao-Ling Huang; Dai-Wei Wang; Ying-Qian Liu; Yong-Xian Cheng (Molecules, 2022)
Six new diterpenoids, blusamiferoids A–F (1–6), including four pimarane-type diterpenoids, one rosane-type diterpenoid (3), and one rearranged abietane-type diterpenoid (6), were isolated from the dry aerial parts of Blumea balsamifera. Their structures were characterized by spectroscopic and computational methods. In particular, the structures of 1 and 4 were confirmed by X-ray crystallography. Compounds 5 and 6 were found to dose-dependently inhibit the production of TNF-α, IL-6, and nitrite oxide, and compound 5 also downregulated NF-κB phosphorylation in lipopolysaccharide (LPS)-induced RAW 264.7 cells.